Analysis of L Antigen Family Member 3 as a Potential Biomarker and Therapeutic Target Associated With the Progression of Hepatocellular Carcinoma - Chen, Qianhui; Lu, Xinyu; Xie, Jiayi; Ma, Na; Xu, Weikang; Zhang, Zhiming; Huang, Xuan; Liu, Hongyan; Hou, Jinlin; Zhang, Xiaoyong; Zhu, Wei (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma (HCC) is the third cause of cancer-related deaths worldwide. L antigen family member 3 (LAGE3) is a prognostic biomarker and associated with progression in a variety of tumors. However, little has been reported about the role and potential mechanism of LAGE3 in HCC. Methods: The clinical value and function of LAGE3 in HCC were obtained from multiple online databases. The potential functions and pathways of LAGE3 in HCC were analysed by R package of “clusterProfiler”. LAGE3 knockdown cells were constructed in HepG2, HuH7 and MHCC97H cell lines, respectively. The biological roles of LAGE3 were examined by in vitro and in vivo experiments. Results: LAGE3 was upregulated in HCC tissues compared with normal tissues, and high expression of LAGE3 was significantly associated with several clinical characteristics and indicated a worse prognosis of HCC. The co-expressed genes of LAGE3 could be enriched in the mTOR signaling pathway in HCC. LAGE3 was upregulated in HCC cell lines. Functionally, knocking down LAGE3 expression not only increased apoptosis and inhibited growth rate, cell death mediated by T cells, colony formation, migration and invasion ability of HCC cell lines in vitro, but also reduced the progression of HCC in the subcutaneous xenotransplanted tumor model. Conclusion: Our results suggested that LAGE3 served as an oncogenic factor of HCC and could be a potential biomarker and therapeutic target for HCC.